Analysis of Ticket Purchase Behavior at Mawar Tour & Travel Pekalongan - Ade Putri Nurudina (Shipping and Transport Management Journal, 2025)
This study aims to analyze ticket purchasing behavior at Mawar Tour & Travel Pekalongan. The issue raised in this research is the decline in direct ticket purchases due to the rise of competing digital platforms, which has made it more challenging for traditional travel agencies to retain customers. The research method used is quantitative, employing multiple linear regression analysis through SPSS software to evaluate various factors influencing customer decisions. The results show that service quality and price perception significantly affect purchase intention, while booking convenience does not directly influence it but is fully mediated by trust, highlighting the importance of building strong customer relationships. These findings suggest that Mawar Tour & Travel should enhance service quality, strengthen customer trust, and adopt competitive pricing strategies to improve customer satisfaction and increase sales. This approach would enable the agency to stay competitive in the rapidly changing digital marketplace and better meet the needs of its customers.